2016
DOI: 10.1128/iai.00235-16
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter saguini, a Novel Helicobacter Isolated from Cotton-Top Tamarins with Ulcerative Colitis, Has Proinflammatory Properties and Induces Typhlocolitis and Dysplasia in Gnotobiotic IL-10 −/− Mice

Abstract: A urease-negative, fusiform, novel bacterium named Helicobacter saguini was isolated from the intestines and feces of cottontop tamarins (CTTs) with chronic colitis. Helicobacter sp. was detected in 69% of feces or intestinal samples from 116 CTTs. The draft genome sequence, obtained by Illumina MiSeq sequencing, for H. saguini isolate MIT 97-6194-5, consisting of ϳ2.9 Mb with a G؉C content of 35% and 2,704 genes, was annotated using the NCBI Prokaryotic Genomes Automatic Annotation Pipeline. H. saguini contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 51 publications
(69 reference statements)
1
24
0
Order By: Relevance
“…Recently, we demonstrated that H. saguini infection in a gnotobiotic IL‐10 −/− mouse model elicits inflammatory and dysplastic changes to the large intestine, suggesting an etiological role of H. saguini infection in the pathogenesis of IBD in captive CTTs (Shen et al, ). Although EHS infection is strongly associated with gastrointestinal inflammation and cancer progression, the mechanisms by which H. saguini and other EHS colonise their host and cause disease are only elucidated in part and require further studies (Shen et al, ; Whary & Fox, ; Young et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we demonstrated that H. saguini infection in a gnotobiotic IL‐10 −/− mouse model elicits inflammatory and dysplastic changes to the large intestine, suggesting an etiological role of H. saguini infection in the pathogenesis of IBD in captive CTTs (Shen et al, ). Although EHS infection is strongly associated with gastrointestinal inflammation and cancer progression, the mechanisms by which H. saguini and other EHS colonise their host and cause disease are only elucidated in part and require further studies (Shen et al, ; Whary & Fox, ; Young et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, GGT appears to be important because its activity has been shown to promote hose colonisation, proinflammatory responses, and intestinal pathology. Furthermore, biochemical characterisation of H. saguini detected GGT activity (Shen et al, ). Therefore, the aim of this study was to determine if H. saguini expresses an enzymatically active GGT gene with virulence properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the inflammatory lesions found at necropsy, the colony from which H. jaachi was isolated was noted to have clinical gastrointestinal disease as evidenced by sporadic cases of diarrhea and chronic weight loss [63]. The finding of IBD, sometimes in conjunction with colon adenocarcinoma or hepatobiliary inflammatory changes, is reminiscent of findings reported in other nonhuman primates (NHPs) infected with Helicobacter spp [64e68].…”
Section: Clinical Signsmentioning
confidence: 92%
“…The influence of H. pylori on CD activity merits further investigation; there are protective effects of this gastric infection for IBD, which may be linked to the cag A‐positive status of the strain . A model using the non‐human primate Helicobacter, Helicobacter saguini, seems to be useful to study the pathogenic potential of EHS isolated from primates with naturally occurring IBD …”
Section: Miscellaneousmentioning
confidence: 99%